IMPLEMENTATION OF DISCIPLINE CHARACTER EDUCATION IN EARLY CHILDHOOD (MUL-TI-SITE STUDY IN TUNAS BANGSA AND AISYIYAH BUSTANUL ATHFAL INTEGRATED EARLY CHILDHOOD EDUCATION AT GOLF LANDASAN ULIN) - Mahmudah, Laila; Asniwati; Aslamiah (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The research aims to describe and analyze the Planning, Strategy, and Evaluation of the implementation of disciplined character education in Tunas Bangsa Integrated PAUD and Aisyiyah Bustanul Athfal Golf Integrated Course in Ulin. The results showed: Planning involves foundations, principals, teachers, and education personnel, to formulate policies, set regulations, through meetings, involve parents, and be socialized at the beginning of the school year. Referring to the 2013 Curriculum, 9 pillars of character and K4 from IHF, training, are integrated in the implementation of learning. Implementation strategy: socialization of regulations, integrated in every lesson. Through habituation, example, protecting attitude, caring, caring, punishment, rewards (consequences), motivation, and consistency. The constraints to its application are in the family and school environment. Evaluation of school regulations by the Foundation, school principals, teachers and educators by identifying problems, deliberations, gathering information, determining solution criteria (follow-up) according to the school's vision, mission, goals. Evaluation of aspects of learning: observation, checklist, daily notes, anecdotes